Strategy of Islamic Education Teachers in Instilling Character Values Based on Digital Ethics Among Students At SMK Negeri 4 Tanjungbalai City - Al Hujrat Rambe; Mhd. Habibu Rahman (Hikmah, 2025)
The phenomenon of digital media misuse among students—such as the spread of hoaxes, hate speech, and cyberbullying—indicates a low awareness of digital ethics. This condition demands the educational sector, particularly Islamic Religious Education, to play an active role in shaping students’ character so they can use technology wisely and in accordance with Islamic values. This study aims to explore the strategies employed by Islamic Education teachers in instilling character values based on digital ethics among students at SMK Negeri 4 Tanjungbalai City. The study uses a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings show that Islamic Education teachers apply integrative strategies combining Islamic teachings with digital phenomena through role modeling, habituation, and contextual discussions on current digital issues. These strategies effectively enhance students’ moral awareness and sense of responsibility in digital spaces. However, low digital literacy and limited facilities remain obstacles. Therefore, collaboration among teachers, schools, and parents is essential to strengthen students’ digital character grounded in Islamic values.